Direct three-dimensional imaging of polymer-water interfaces by nanoscale hard X-ray phase tomography - Cheng, Yin; Suhonen, Heikki; Helfen, Lukas; Li, Junsheng; Xu, Feng; Grunze, Michael; Levkin, Pavel; Baumbach, Tilo (Soft matter, 2014)
We report three-dimensional (3D) direct imaging of complex surface-liquid interfaces by hard X-ray phase contrast tomography as a non-destructive approach for the morphological characterization of surfaces at the micro- and nanoscale in contact with water. Specifically, we apply this method to study the solid-air-water interface in hydrophobic macroporous polymethacrylate surfaces, and the solid-oil-water interface in slippery liquid-infused porous surfaces (SLIPS). Varying the isotropic spatial resolution allows the 3D quantitative characterization of individual polymer globules, globular clusters (porosity) as well as the infused lubricant layer on SLIPS. Surface defects were resolved at the globular level. We show the first application of X-ray nanotomography to hydrated surface characterizations and we anticipate that X-ray nanoscale imaging will open new ways for various surface/interface studies.
Gesehen am 27.10.2020